JAM KERJA PANJANG DAN MINIMNYA PENGHARGAAN: DINAMIKA MOTIVASI KERJA KARYAWAN USAHA KULINER DI KOTA - Parman, Parman; Agussalim, Agussalim; Vadilla, Zafitri Nur; Heriyani, Veni; Ask, Hilman Van; Saputra, Hendriky (STIE Mahardhika, 2026)
This study aims to analyze the factors causing low work motivation among employees in the culinary business, particularly cafes, in Parepare City and to formulate strategic recommendations for increasing work motivation. The research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research informants consisted of eight cafe employees with diverse job backgrounds and lengths of service. The results showed that employee work motivation tended to be low and unstable, mainly influenced by internal factors such as a lack of reward systems, limited opportunities for self-development, and weak motivational communication from management. In addition, external factors such as an suboptimal compensation system, long working hours, high workload during busy hours, and limited managerial support also contribute to low work motivation. These conditions have an impact on decreased work enthusiasm, task effectiveness, teamwork, and service quality. This study emphasizes the importance of structured work motivation management through the implementation of a reward system, proportional working hours, employee training, and the creation of a conducive work environment. These findings provide empirical contributions to the study of work motivation in culinary MSMEs in the context of small cities and can serve as a practical reference for managers.